2003
DOI: 10.1246/cl.2003.614
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ring Expansion of the Holey Ketolactam Derivative of C60

Abstract: The migrative addition reaction of phenylhydrazine to the ketolactam derivative of C60 occurred with a regioselective cage scission to give a 15-membered ring-opened fullerene bearing a methylene carbon and an acenaphthenequinone monophenylhydrazone unit along the orifice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…47 One methylene carbon was confirmed by both 1 H NMR and 13 C NMR spectra as described in the case of 11. In a similar way, the sequential cage scission reaction of 1 with ortho-phenylenediamine proceeded at 80 °C in the presence of an excess amount of pyridine to give 18a in 37% yield.…”
Section: Expansion Of the Orifice Of The Open-cage Ketolactam C 60mentioning
confidence: 70%
“…47 One methylene carbon was confirmed by both 1 H NMR and 13 C NMR spectra as described in the case of 11. In a similar way, the sequential cage scission reaction of 1 with ortho-phenylenediamine proceeded at 80 °C in the presence of an excess amount of pyridine to give 18a in 37% yield.…”
Section: Expansion Of the Orifice Of The Open-cage Ketolactam C 60mentioning
confidence: 70%
“…[44] The reaction of amino-compounds with open-cage fullerene derivatives is an efficient method to form large holes capable of incorporating small molecules. [52] Iwamatsu and coworkers found that hydrazine or hydrazone or phenylenediamine reacted with the ketolactam 25 to form compounds 44 [53] and 45.…”
Section: Hole-enlargement Reactionsmentioning
confidence: 99%
“…The similar reaction was applied to ketolactam 20 by Iwamatsu and co-workers in 2003 [80] and tested by Orfanopoulos and co-workers in 2004 [81] (Scheme 9.32) to give a product with a 15-membered-ring orifice, whose structure was claimed to be 59 by the former and 60 by the latter. The difference in the structure between 59 and 60 arose from which of the two CbC double bonds, (a) or (b), was cleaved.…”
Section: Open-cage Fullerenes To Endohedral Fullerenes 403mentioning
confidence: 98%
“…The reaction of 51 with aromatic hydrazines gave 58 having a 16-membered-ring orifice in 50-89% yields (Scheme 9.31)[79].Scheme 9.28. Photooxygenative ring enlargement of 46.…”
mentioning
confidence: 99%